Hubungan antara Pola Asuh Orang Tua dengan Hasil Belajar Siswa SD Kelas V - Elizabeth Meiske Maythy Lasut; Ribka BR Sembiring; Anita Ole (Journal on Education, 2023)
This descriptive and correlative quantitative research was carried out to prove the relationship between parenting style and student learning achievement. In collecting the required data, researchers conducted a survey containing questionnaire adapted from the instrument constructed by Puspicahyani (2006) about parenting style. In addition, learning achievement data is taken from the results of the midterm exams. The respondents to this study consisted of 60 grade V students of Airmadidi Adventist Elementary School. The results of the study indicate that democratic parenting is the parenting style that students experience more often than authoritarian or permissive parenting. As for learning achievement, the students are able to show good learning achievement in general. In addition, the results of the study also proved that a significant relationship occurred between democratic parenting style and students’ learning achievement, however, no significant relationships found between two other parenting styles and students’ learning achievement. That is why it is recommended for parents to better apply parenting democratically in guiding their children so that maximum results in learning can be achieved.